Security on ROS: analyzing and exploiting vulnerabilities of ROS-based systems - Teixeira, Rafael R.; Maurell, Igor P.; Drews, Paulo L.J. (Proceedings (Brazilian Robotics Symposium. Online), 2020)
Over the past years humans and robots sharing environments have become increasingly common. As developers and researchers often focus on innovation and functionality, security usually becomes an overlooked topic. However, security issues in robotic systems can become a threat to the human life when exploited, which makes security in robotic systems an even more critical subject. The Robot Operating System (ROS) is one of the most adopted frameworks on research and developments of robotics, however, it has a lot of security issues. In this paper, we take a closer look in the common vulnerabilities that ROS-based systems share and the dangers that those could lead to human-robot shared environments. We have created a tool that can intercept, manipulate and completely disrupt the communication between two ROS nodes. The tool was tested on a robot called DoRIS, an autonomous domestic robot. Our results show that it is possible to completely compromise ROS-based robots by taking control of the communication between its nodes.